1998
DOI: 10.1063/1.121168
|View full text |Cite
|
Sign up to set email alerts
|

Intense photoluminescence from self-assembling InGaN quantum dots artificially fabricated on AlGaN surfaces

Abstract: We demonstrate photoluminescence (PL) from self-assembling InGaN quantum dots (QDs), which are artificially fabricated on AlGaN surfaces via metalorganic chemical vapor deposition. InGaN QDs are successfully fabricated by the growth mode transition to three-dimensional nanoscale island formation by using “antisurfactant” silicon on AlGaN surface. The diameter and height of the fabricated InGaN QDs are estimated to be ∼10 nm and ∼5 nm, respectively, by an atomic-force microscope (AFM). Indium mole fraction of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
69
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(71 citation statements)
references
References 14 publications
2
69
0
Order By: Relevance
“…As a possible origin, Ruminov et al suggested that Si mostly affects the dislocation structure during the GaN growth, perhaps by changing the atom mobility and the number of growth islands at the initial stage of the growth, and/or changing the dislocation mobility. Aoyagi and co-workers [23][24][25] have used the influence of silicon on the growth of GaN, InGaN, and AlGaN to grow quantum dots. In these studies it has been demostrated that silicon acts as a surfactant at the initial stages of growth, inducing a three-dimensional Stranski-Krastanow growth mode.…”
Section: Discussionmentioning
confidence: 99%
“…As a possible origin, Ruminov et al suggested that Si mostly affects the dislocation structure during the GaN growth, perhaps by changing the atom mobility and the number of growth islands at the initial stage of the growth, and/or changing the dislocation mobility. Aoyagi and co-workers [23][24][25] have used the influence of silicon on the growth of GaN, InGaN, and AlGaN to grow quantum dots. In these studies it has been demostrated that silicon acts as a surfactant at the initial stages of growth, inducing a three-dimensional Stranski-Krastanow growth mode.…”
Section: Discussionmentioning
confidence: 99%
“…The aspect ratio (height/diameter) of the In-rich InGaN QDs was below 0.1, which is similar to that of InN QDs, 25) and it is much lower than that SELECTED TOPICS in APPLIED PHYSICS III of Ga-rich InGaN QDs. [26][27][28] We suppose that In-rich InGaN QDs have lower aspect ratios because of the rapid decomposition of In-rich InGaN at the apex regions of QDs as we observed in our In-rich InGaN/GaN QW structures. 10,12) The In-rich InGaN/GaN QDs were capped with GaN at 650 C to enable investigation of their optical properties.…”
Section: Resultsmentioning
confidence: 78%
“…Here, a key question is how to form the AlGaN/GaN-based nanostructures in a size-and position-controlled manner. Recent studies on the fabrication of GaN-based quantum structures have been mostly focused on the self-assembled formation of quantum dots (QDs) using the Stranski-Krastanov mode [1,2] or anti-surfactant methods [3,4]. In these methods, control of size and position seems to be very difficult.…”
Section: Introductionmentioning
confidence: 99%